Bentuk dan Fungsi Tindak Tutur Asertif dalam Serial Animasi Nussa: The Movie serta Pemanfaatannya dalam Pembelajaran Teks Eksposisi di SMP - Alya Desi Nafallillah; Slamet Mulyono (Simpati, 2026)
This study aims to describe the forms and functions of assertive speech acts in the animated film “Nussa: The Movie” and their utilization in expository text learning in junior high school. The study employs a descriptive qualitative approach. Data consist of character utterances collected through observation and note-taking techniques. Data validity was tested using theory triangulation and persistent observation. The theoretical framework includes Austin and Searle's (1979) speech act theory, as well as perspectives from Arnaselis and Rusminto (2017), Lailika and Utomo (2020), Minarti and Wijayanti (2020), and Fakhriyah (2020). Results reveal 83 assertive speech act data across seven forms, namely expressing opinion (15, 18.1%), mentioning (11, 13.3%), informing (14, 16.9%), showing (7, 8.4%), reporting (14, 16.9%), boasting (10, 12.0%), and claiming (12, 14.5%). Each form has a distinctive illocutionary speech function, namely conveying arguments, presenting factual data, informing new knowledge, reinforcing statements with evidence, objectively reporting events, expressing fact-based appreciation, and asserting beliefs. These seven forms are closely related to expository text characteristics, making them applicable in expository text learning in junior high school in accordance with the Merdeka Curriculum.